ПРЕЗИДЕНТИМИЗ И.А. КАРИМОВТЫҢ «ЖОҚАРЫ МӘНАЎИЯТ – ЖЕҢИЛМЕС КҮШ» АТЛЫ МИЙНЕТИ - ИЛИМИЙ ИЗЕРТЛЕЎЛЕРДИҢ ТЕОРИЯЛЫҚ ҲӘМ МЕТОДОЛОГИЯЛЫҚ ҚУРАЛЫ - Базарбаев, Ж. (FAN va JAMIYAT, 2016)
The article deals with the role and significance of the work. «High spirituality – unwinming strength» by the President of the Republic of Uzbekistan I.A.Karimov in the protection of material and spiritual values. The author of the article states that the issues of revival and protection of national values, their role in the spiritual development of people became the main theme of the seminar, organized at the institute.